2014
DOI: 10.1002/ejoc.201402475
|View full text |Cite
|
Sign up to set email alerts
|

Nickel‐Catalyzed One‐Pot Suzuki–Miyaura Cross‐Coupling of Phenols and Arylboronic Acids Mediated by N,N‐Ditosylaniline

Abstract: An efficient method for the construction of two distinct Caryl–Caryl bonds through the Ni‐catalyzed Suzuki–Miyaura cross‐coupling of phenols with arylboronic acids has been developed. This reaction proceeds through the in situ tosylation of phenols by using N,N‐ditosylaniline as the sulfonylating reagent, which is highly active, markedly stable, and easily prepared. The scope with respect to the coupling partners – phenols and boronic acids – is broad, and sensitive functional groups are tolerated. Phenols, es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…The one-pot in situ activation of C-O bonds of phenols with novel N,N-ditosylaniline to generate the corresponding tosylate for the catalytic cross-coupling reaction with arylboronic acid was reported in 2014 by Yu, Wang and coworkers (Scheme 6B). 12 NiCl 2 (dppp) was employed for the C-O bond cleavage of the aryl tosylate (formed in situ). A broad scope of arylboronic acids and phenols were smoothly transformed to furnish biaryls containing chloride, fluoride, cyanide, ether, ester, formyl, acetyl, or even free amine in fair to excellent yields (30-94%).…”
Section: Scheme 6 Nickel-catalyzed Suzuki-miyaura-type Cross-couplingmentioning
confidence: 99%
“…The one-pot in situ activation of C-O bonds of phenols with novel N,N-ditosylaniline to generate the corresponding tosylate for the catalytic cross-coupling reaction with arylboronic acid was reported in 2014 by Yu, Wang and coworkers (Scheme 6B). 12 NiCl 2 (dppp) was employed for the C-O bond cleavage of the aryl tosylate (formed in situ). A broad scope of arylboronic acids and phenols were smoothly transformed to furnish biaryls containing chloride, fluoride, cyanide, ether, ester, formyl, acetyl, or even free amine in fair to excellent yields (30-94%).…”
Section: Scheme 6 Nickel-catalyzed Suzuki-miyaura-type Cross-couplingmentioning
confidence: 99%
“…21 Recently, Chen et al reported an efficient nickel-catalyzed one-pot Suzuki−Miyaura cross-coupling of phenols and arylboronic acids mediated by N,N-ditosylaniline. 22 The one-pot activation strategy possesses important advantages in comparison to a stepwise method. First, the preactivation step limits the efficiency of a two-step protocol in view of overall yields and step economy.…”
mentioning
confidence: 99%
“…To use phenolic compounds in coupling reactions, there are two strategies. In the most widely used method (stepwise), phenols are first converted to the corresponding aryl C–O electrophile and then used for the next reaction. One-pot activation of phenols is another approach for the generation of an active coupling partner in metal-catalyzed cross-coupling reactions. Bromo-trispyrrolidino phosphonium­hexafluoro­phosphate is the most widely used reagent for one-pot activation of phenolic compounds . In some cases, phenolic salts were used in the one-pot activation process .…”
mentioning
confidence: 99%
See 2 more Smart Citations